2004
DOI: 10.1097/01.wnr.0000134472.44362.be
|View full text |Cite
|
Sign up to set email alerts
|

Reduced basal forebrain and hippocampal activation during memory encoding in girls with fragile X syndrome

Abstract: Fragile X syndrome (FraX), the most common heritable cause of developmental disability, is associated with IQ, memory, and visuospatial processing deficits. The fragile X gene (FMR1) is prominently transcribed in two regions critical to memory encoding and attention: the hippocampus and the basal forebrain. To probe functional MRI activation abnormalities associated with the disorder, girls with FraX and age-matched, normally-developing girls were scanned during a test of visual memory encoding. While there we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…While the hippocampus itself may be enlarged, individuals with FXS show reduced hippocampal activation during visual memory encoding (Greicius et al, 2004), as well as deficits in episodic memory (de von Flindt et al, 1991). Taken together, these findings lend support to the idea that the Fmr1 gene plays an important role in hippocampal structural development and thus the proper functioning of the hippocampus.…”
Section: Hippocampal Neuropathology In Fxs Patientsmentioning
confidence: 85%
“…While the hippocampus itself may be enlarged, individuals with FXS show reduced hippocampal activation during visual memory encoding (Greicius et al, 2004), as well as deficits in episodic memory (de von Flindt et al, 1991). Taken together, these findings lend support to the idea that the Fmr1 gene plays an important role in hippocampal structural development and thus the proper functioning of the hippocampus.…”
Section: Hippocampal Neuropathology In Fxs Patientsmentioning
confidence: 85%
“…For example, in a study of episodic memory in females [Greicius et al, 2004], results indicated decreased activation in the hippocampus and basal forebrain for girls with FraX compared to their typically developing peers. In conjunction with the finding that high levels of FMR1 mRNA occurs in both of these brain regions during human fetal development [Abitbol et al 1993] and the knowledge that cholinergic pathways in the basal forebrain and hippocampus are critical to numerous important cognitive functions, these data provided motivation to design a clinical trial of a medication intended to enhance cholinergic neurotransmission in the brain and subsequently improve learning and memory [Kesler et al, 2009].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study using fMRI during visual memory encoding uncovered decreased activation in the hippocampus and orbital regions of the frontal cortex [Greicius et al, 2004]. Other studies have reported volumetric abnormalities in select brain regions, including the hippocampus [see Hessl et al, 2004 for review].…”
Section: Fragile X Syndromementioning
confidence: 98%